2013
DOI: 10.1108/jcs-07-2013-0024
|View full text |Cite
|
Sign up to set email alerts
|

Implementing mindfulness and yoga in urban schools: a community-academic partnership

Abstract: Purpose – Mindfulness-based interventions – which train capacities for attention, awareness, compassion, and self-regulation of thoughts and emotions – may offer unique benefits for urban youth exposed to chronic stress and adversity. Urban schools are promising settings in which to integrate mindfulness-based interventions; however, they pose complex challenges for intervention implementation and evaluation. Design/methodology/approach – The paper reflects on the experiences of our community-academic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 32 publications
0
30
0
3
Order By: Relevance
“…Indeed, anecdotal reports from study staff and the yoga instructors suggested that some of the physical education teachers were expressing concerns to students such as yoga not providing enough of a workout for students to succeed on state-mandated fitness testing. Previous research suggests that support from teachers and administrative staff is essential to the success of school-based yoga (Mendelson et al 2013; Miller et al 2014), thus the relatively low levels of physical education teacher buy-in may have influenced the present results.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, anecdotal reports from study staff and the yoga instructors suggested that some of the physical education teachers were expressing concerns to students such as yoga not providing enough of a workout for students to succeed on state-mandated fitness testing. Previous research suggests that support from teachers and administrative staff is essential to the success of school-based yoga (Mendelson et al 2013; Miller et al 2014), thus the relatively low levels of physical education teacher buy-in may have influenced the present results.…”
Section: Discussionmentioning
confidence: 78%
“…While a small number of studies have discussed the feasibility, acceptability, and sustainability of school-based yoga and mindfulness programming (Dariotis et al, 2017; Feagans Gould, Dariotis, Greenberg, & Mendelson, 2016; Mendelson et al, 2013; Zenner et al., 2014), these topics are largely absent from the literature. The current study addresses this limitation by examining students’ personal perceptions of a school-based yoga program.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, these interventions can be seen as a strategy to enhance self-care resources for staff and promote mental health among professionals (Christopher, Christopher, Dunnagan, & Schure, 2006;Franco et al, 2010) and students, in the case of teachers, when faced with, for example, high levels of stress during exam periods (Álvarez et al, 2012;Langer et al, 2015;Mendelson et al, 2013;Zenner, Herrnleben-Kurz, & Walach, 2014).…”
Section: Discussionmentioning
confidence: 99%